2007
DOI: 10.1186/1477-7525-5-40
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of an abbreviated version of the Child-OIDP inventory among primary schoolchildren in Tanzania

Abstract: Background: There is a need for studies evaluating oral health related quality of life (OHRQoL) of children in developing countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

34
107
9
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(152 citation statements)
references
References 23 publications
34
107
9
2
Order By: Relevance
“…Inter-item correlations matrix for the C-OIDP scale adapted to chilean school children aged 11 to 14 years old. *p<0.05 18 , with the exception of Tanzania where the value was 0.77 16 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Inter-item correlations matrix for the C-OIDP scale adapted to chilean school children aged 11 to 14 years old. *p<0.05 18 , with the exception of Tanzania where the value was 0.77 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Was conducted a cross-cultural adaptation of the Child-OIDP survey previously used in a validation study in Spain 7 and followed the guidelines previously used in other validation studies [13][14][15][16][17][18] . The experience of pediatric dental professionals, who knew the terms used by children regarding oral health, was important in the modification process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13,14 The CPQ [8][9][10] was developed by Jokovic et al, 4 and translated and validated to be used in Brazil by Barbosa et al 15 This assessment tool is widely used in children, addressing issues concerning oral symptoms, functional limitations, emotional well-being, social welfare, global oral health and the extent to which oral health affects the general well-being. 13,14,15,16,17,18,19 The prevalence of impact on OHRQoL observed in previous studies using this assessment tool has ranged from 29.5% to 94.8%, with the "oral symptoms" domain reported as the most negatively affected. 20, 21,22,23 The child-OIDP was developed by Gherunpong et al, 5 and translated and validated for the Brazilian population by Castro et al 14 This index evaluates the impact of oral health in the quality of life through eight daily activities (eating, speaking, mouth cleaning, sleeping, smiling, emotional status, studying, and social contact).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies using child-OIDP have reported the prevalence of impact on OHRQoL ranging from 28.6% to 89.8%. 6,16,17,18 Among these studies, the "eating" daily activity has been the most negatively affected activity.…”
Section: Introductionmentioning
confidence: 99%